Fleeing the “Harem,” embracing Europe : space, identity and discourse in Melek Hanım’s autobiographical texts : “Harem”den kaçmak, Avrupa’yı kucaklamak : Melek Hanım’ın otobiyografik metinlerinde mekan, kimlik ve söylem - Küçükturan, Fatma Şevval. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis problematizes the construction of the discourse through identity and space in Melek Hanım's autobiographical texts, Thirty Years in the Harem (1872) and Six Years in Europe (1873), which was published under the name Kıbrıslı Mehmed Emin Paşa’s wife. It argues that as the place shifts, the identities of the narrator also change, and Melek Hanım's discourse takes shape depending on these variables in the aforementioned autobiographical narratives. The shifting identities of Melek Hanım in Eastern and Western spaces have been discussed while asserting that the spatial practices and self-representations in the texts are in a mutual relationship with the construction of the discourse in Thirty Years in the Harem, Melek Hanım reveals her life in the Ottoman lands using the pile of her subjective memory. It was built on an orientalist discourse in which an Ottoman elite narrates Eastern societies and her life experience. Nevertheless, the narrator’s voice embodies a victimized woman's identity in Six Years in Europe, which covers the six-year period that Melek Hanım had spent and experienced after fleeing to Europe. This thesis attempts to elucidate how the construction of discourse among Melek Hanım’s autobiographical texts differs depending on the representations of space and identity.
Keywords: Malik-Khanam, 1814-1873.; Malik-Khanam, 1814-1873. Thirty years in the Harem.; Malik-Khanam, 1814-1873. Six years in Europe.; Women -- Turkey.; Harems.